2022
DOI: 10.1002/cnr2.1736
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative induction of receptor tyrosine kinases contributes to adaptive MAPK drug resistance in melanoma through the PI3K pathway

Abstract: Vemurafenib-induced drug resistance in melanoma has been linked to receptor tyrosine kinase (RTK) upregulation. The MITF and SOX10 genes play roles as master regulators of melanocyte and melanoma development. Here, we aimed to explore the complex mechanisms behind the MITF/SOX10-controlled RTK-induced drug resistance in melanoma. To achieve this, we used a number of molecular techniques, including melanoma patient data from TCGA, vemurafenib-resistant melanoma cell lines, and knock-down studies. The melanoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our observations are likely not limited to EGFR but could prove valid also for other RTKs that are de novo expressed on VR cells. Among these, AXL is particularly appealing since it is included in the RTK signatures of BRAFi resistant CM (Figure 1A), and it has been proposed to play a potentially important role in acquiring resistance to BRAFi and in increasing the invasive potential of CM cells (24,33,(76)(77)(78). Noteworthy, a recent single cell sequencing study revealed that a population resistant to targeted-therapy labeled as "invasive" and expressing high levels of AXL became frequently expanded in CM patient derived xenografts progressing on combined BRAF/MEK/RXR inhibition (18).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are likely not limited to EGFR but could prove valid also for other RTKs that are de novo expressed on VR cells. Among these, AXL is particularly appealing since it is included in the RTK signatures of BRAFi resistant CM (Figure 1A), and it has been proposed to play a potentially important role in acquiring resistance to BRAFi and in increasing the invasive potential of CM cells (24,33,(76)(77)(78). Noteworthy, a recent single cell sequencing study revealed that a population resistant to targeted-therapy labeled as "invasive" and expressing high levels of AXL became frequently expanded in CM patient derived xenografts progressing on combined BRAF/MEK/RXR inhibition (18).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas cells expressing low levels of MITF have a slow-cycling, mesenchymal-like, pro-invasive phenotype, higher levels of MITF correlate with proliferation and differentiation [ 69 – 72 ]. Interestingly, low MITF levels are also found in drug resistant melanoma cell lines, which was previously defined as hallmark of dormancy [ 73 ]. MITF acts as a “rheostat” and is considered as one of the key regulators of melanoma phenotype switching [ 71 , 74 ].…”
Section: Molecular and Cellular Mechanisms Regulating Melanoma Dormancymentioning
confidence: 99%